Application of the expert assessment method to assessment information risks higher educational institution - Ткач, Юлія Миколаївна; Казмірчук, Світлана Володимирівна; Мехед, Дмитро Борисович; Базилевич, Володимир Маркович (Ukrainian Information Security Research Journal, 2017)
In the article the method of expert evaluations and especially its application as an example the evaluation of information risks of higher education. The main feature of this method is that it is used in cases where the solution of the complicated mathematical methods. Due to the lack of reliable information static or even its absence on information security threats, the most common method of risk assessment information is the method of expert evaluations. Schematically presented action sequences according to the method of expert ratings formulating research objectives, the selection of experts and the formation of a task force drafting questionnaires, surveys, processing and analysis of expert opinion. A statistical tools for processing and analysis of the results of questioning of experts.